THE IMPLEMENTATION OF VIRTUAL PBL (PROJECT BASED LEARNING) MODEL IN ENGLISH DRAMA COURSE - Sandra Dewi Dahlan (UIN Alauddin Makassar, 2022)
This study aimed to describe the implementation of Virtual Project Based Learning model in English Drama course and to evaluate students’ response toward the implementation. This study used mixed methods to integrate the qualitative and quantitative data. The subjects of the study were fourth semester students of class AG 5/6 of English and Literature Department, Faculty of Adab and Humanities, UIN Alauddin Makassar. The object of research is English Drama course by applying the Project Based Learning model in the form of virtual drama performance. The research technique was carried out by means of observation, interviews and surveys to answer research questions. The results showed that most of the students responded positively to the implementation of the virtual drama project and considered the process and implementation successful, especially in providing a positive correlation between drama theory and practice as the learning method in the English Drama course. Despite that the project was carried out online, but students have honed their various soft-skills which also enriched their multiple-intelligence through this Virtual Drama project. Keywords: Virtual Drama, PBL, Students Project, English Drama